Von Willebrand disease as a significant risk factor for hemorrhage after cervical loop electrosurgical excision - Ungure, Anita; Žodžika, Jana; Kuņicina, Diāna; Lietuviete, Nellija; Rezeberga, Dace (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Loop electrosurgical excision procedure (LEEP) is the first-line treatment for cervical intraepithelial neoplasia (CIN). It is effective, easy to perform and relatively safe for the patient. However, 1-2% of patients experience complications such as hemorrhage and infection, which usually are effectively treated using cauterization and antibiotics. We are presenting a case of repeated cervical and vaginal hemorrhage after the cervical LEEP for a patient without previous medical history of severe bleeding or detected bleeding disorders. A generally healthy 38-year-old female underwent planned LEEP of cervix because of CIN II-III. Procedure was successful. Afterwards she was admitted to the Emergency department several times because of recurrent vaginal and cervical bleeding. She received suturing and coagulation of the cervix and vaginal wall combined with desmopressin and tranexamic acid therapy. Because of suspected bleeding disorder hematologist was invited. Laboratory analysis showed positive results for von Willebrand disease. After VIII/von Willebran factor concentrate treatment bleeding was stopped completely. Before any surgical interventions it is important to take a detailed medical history. If atypical, recurrent and/or severe secondary hemorrhage after the surgical manipulations occur, coagulation disorders should be excluded.